Improving assessment methods for freezing of gait in people with Parkinson’s disease - Scully, Aileen Eugenia (Curtin University, 2022)
This thesis aimed to provide a clinician-rated assessment tool for freezing of gait (FOG) severity because existing ones were found to be inadequate in a systematic review. To develop the tool, another systematic review, a Delphi study, and a study examining reliability of video-analysis methods were conducted. The measurement properties of the tool were examined in a cross-sectional study. The FOG Severity Tool is valid and reliable for assessing FOG severity in people with Parkinson’s.